Wide Survey on Online Teaching and Learning During Movement Control Order in Malaysia due to Covid-19 Pandemic - Ahmad Hata, Rasit; Hamimah, Ujir; Chen, Chwen Jen; Rohana, Sapawi; Irwandi Hipni, Mohamad Hipiny (Human Resource Management Academic Research Society, 2021)
“Prepare for the new norm” is a common saying among Malaysians since the federal government introduced the Movement Control Order on March 18th, 2020. Among the many enforced measures to control the spread of the Covid-19 virus are the stay-at-home ruling and the ban on mass gatherings. These measures force Higher Education providers (HEPs) to drastically change the way Teaching and Learning (T&L) activities are conducted at their institutions. Conventional guided face-to-face (f2f) T&L and assessments are no longer tenable; the only workable solution is converting the remaining course plan to full online mode. Universiti Malaysia Sarawak’s (UNIMAS) students and academics are relatively familiar with the concept of blended learning. UNIMAS had started using Learning Management System two decades ago and the current system, e-Learning Enrichment and Advancement Platform or eLEAP, is actively used by all UNIMAS students. However, most of the courses were designed with blended learning relegated to supporting act status; existing only to complement the guided f2f T&L activities. The Movement Control Order (MCO) requires blended learning to be delivered in substitution mode, which is to replace the f2f sessions instead of merely complementing them. To assess the status of UNIMAS’s academics and students for this scenario, an online survey was conducted from March 22nd till March 31st. A total of 640 academics and 6,871 students had participated in the survey. This paper reports on the survey findings that provide insights on how to mitigate the infrastructure and policy shortcomings as to afford effective blended learning (in substitution mode) delivery in UNIMAS as well as to minimise inequitable education for students from diverse online learning readiness.